Uncovering caterpillar fungus (Ophiocordyceps sinensis) consumption patterns and linking them to conservation interventions. Issue 8 (7th July 2022) - He, Jun; Smith‐Hall, Carsten; Zhou, Wen; Zhou, Weijia; Wang, Yunshang; Fan, Ben
Abstract: Wildlife trade threatens global taxa. While interest in consumer behavior is increasing, such studies are scarce, particularly for plants and fungi, around questions of consumer characteristics, preferences, and perceptions. Moreover, these factors are not often marshaled to support conservation measures effectively. To address these questions, we examined the case of Chinese caterpillar fungus ( Ophiocordyceps sinensis [Berk.] G.H. Sung, J.M. Sung, Hywel‐Jones, & Spatafora) consumers. This product is particularly interesting due to its extremely high value, economic importance to harvesters, and increasing conservation concerns. Data were generated through an online structured survey ( n  = 1861 consumers) and semi‐structured qualitative interviews ( n  = 65) across six provinces that comprise the primary market in China. We found significant regional and demographic differences in consumer characteristics, preferences for the geographical origin of the product, and limited understanding of harvester and sustainability issues. Interestingly, consumers in higher income provinces bought less frequently but spent more money with the aim of self‐consumption, compared with consumers in lower income provinces who buy more frequently, spending less, and with the intention to use purchased products as presents for family or friends. Consumer responses indicated that conservation measures can be enhanced through public information dissemination about product characteristics and linking consumers to the consequences of their consumption choices, with a particular focus on geographically differentiated information campaigns.